Sleep Late Impact on The Salivary pH Levels and Amylase Activity among Male Students who has Different BMI Category - Yurnaliza (International Journal of Ecophysiology, 2022)
The lack of sleep could damage the circadian rhythm, which has implications for health issues. Here we conduct a survey on Students from the Faculty of Social and Political using purposive random sampling, by targeting student who has sleep duration low than 8 hours. We are using a questionnaire to gain information about the sleeping duration and also the Body Mass Index (BMI). Moreover, we also collect saliva samples from the students. pH Universal Indicators are used to measure the pH levels of saliva. We predict the salivary amylase activity by measuring the decrease of the substrate. We found about 27 students have a sleep duration of fewer than 6 hours. Then 19 students have a sleep duration of about 8 - 6 hours. Finally, only 5 students have a sleep duration of more than 8 hours. Our study suggests there is no significant difference between the 3 categories of sleep duration on saliva pH levels and salivary amylase activity. The same for the BMI categories. Although there are small differences sleep duration and BMI is not the major factor influencing the pH levels and amylase activity in saliva